PENDIDIKAN ANAK DALAM LES RECRES DU PETIT NICOLAS KARYA RENE GOSCINNY DAN JEAN-JACQUES SEMPE - Rizki, Nurul Dwi; Latjuba, Ade Yolanda; Masdiana, Masdiana - (JURNAL ILMU BUDAYA, 2019)
The study entitled "Children's Education in Les Récrés du Petit Nicolas by René Goscinny and Jean-Jacques Sempé" aims to describe parenting and the impact of the parenting style on the life of Nicolas. Nicolas is the main character in this short story collection, who is still in his early years. The upbringing he received from his parents at home and the teacher and education staff in the school had shaped his personality. For this reason, a study of this collection of stories uses descriptive analysis with an intrinsic approach. This means that the intrinsic elements of the stories are analyzed based on the concepts and theories of early childhood care. The results of the analysis show that Nicolas's parenting model is the authoritative parenting model. This parenting style describes parents who encourage children to be independent, while still giving control to their children's attitudes and behavior. While the pattern of education in schools leads to authoritarian education which is characterized by interaction with teachers and school supervisors who are limiting, threatening and even punishing. The impact of this upbringing turned out to have made Nicolas, a child who was creative, open and friendly, dared to express opinions, be cooperative and willing to admit mistakes. Nicolas is also sensitive to his surroundings and has high curiosity.